Business opportunities - Hollett, Vicki (Oxford University Press, 1997)
The book is based on a comprehensive language syllabus which is developed in the context of everyday business functions. Its fourteen units provide opportunities for practising the language of a range of specific and general professional situations, such as telephoning to make arrangements, describing products and services, reporting on progress, and planning ahead